Company Responsibility Regarding Compensation for Workers Who Violate PKWT in Semarang City According to PP No. 35 of 2021 - Muhammad Alif; Tri Sulistiyono (Universitas Negeri Semarang, 2026)
This article discusses the obligation of companies to pay compensation to fixed-term contract workers whose employment relationship has ended due to violations committed by the workers based on laws and regulations, company regulations, and collective labor agreements. The purpose of this study is to analyze the mechanism of compensation payment by companies and the responsibility of companies regarding compensation payments to PKWT workers who violate PKWT or company regulations using an empirical juridical research method through analysis of labor regulations and empirical data obtained through observation and interviews with industrial relations mediators from the Semarang City Manpower Office and several company HR departments. Based on the results of observations and interviews, it was found that there was a discrepancy between the provisions of PP No. 35 of 2021 in conjunction with Law No. 13 of 2003 in conjunction with Law No. 6 of 2023 (das sollen), which requires companies to pay compensation to PKWT workers without exception. However, empirically (das sein), there are still many cases of disputes over rights arising because companies do not fulfill this obligation to workers. This situation has created a legal gap between normative provisions and practice in the field. The Constitutional Court Decision No. 168/PUU-XXI/2023, which requires companies to provide compensation without exception, and the Industrial Relations Court Decision No. 203/Pdt.Sus -PHI/2022/PN Jkt.Pst, which states that companies are required to pay compensation to workers, are examples of the legal consequences faced by companies that fail to comply with applicable regulations.